2022
DOI: 10.1186/s13020-021-00555-7
|View full text |Cite
|
Sign up to set email alerts
|

Compound traditional Chinese medicine dermatitis ointment ameliorates inflammatory responses and dysregulation of itch-related molecules in atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is a chronic inflammatory skin disease accompanied with itchy and scaly rash. Compound traditional Chinese medicine dermatitis ointment (CTCMDO) consists of a mixture of extracts from five plants, which had been used in AD treatment due to good anti-inflammatory and anti-allergic effects. Materials and methods In this study, high-performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…As AD pathogenesis shares common features with allergic diseases, such as pro-inflammatory immune responses ( Akdis et al ., 2006 ; Bantz et al ., 2014 ), various anti-inflammatory immune regulators from the natural extracts of medicinal plants have shown therapeutic potentials in AD ( Ku et al ., 2018 ; Song et al ., 2019 ; Bai et al ., 2020 ). Notably, from the previous studies, we understand that a common mode of action of natural products exists, i.e., by suppression of MAPKs and NF-κB ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Thus, by using NJK14047, a potent and specific p38 MAPK inhibitor, for the first time, we recognized the importance of p38 MAPK inhibitors to develop novel anti-AD drugs because p38 MAPK inhibition distinctly leads to the suppression of the immune responses of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As AD pathogenesis shares common features with allergic diseases, such as pro-inflammatory immune responses ( Akdis et al ., 2006 ; Bantz et al ., 2014 ), various anti-inflammatory immune regulators from the natural extracts of medicinal plants have shown therapeutic potentials in AD ( Ku et al ., 2018 ; Song et al ., 2019 ; Bai et al ., 2020 ). Notably, from the previous studies, we understand that a common mode of action of natural products exists, i.e., by suppression of MAPKs and NF-κB ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Thus, by using NJK14047, a potent and specific p38 MAPK inhibitor, for the first time, we recognized the importance of p38 MAPK inhibitors to develop novel anti-AD drugs because p38 MAPK inhibition distinctly leads to the suppression of the immune responses of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the effectiveness of traditional Chinese medicines and their active components in treating AD ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Interestingly, suppression of AD by traditional Chinese medicines has been reported to be mediated through the inhibition of mitogen-activated protein kinases (MAPKs), such as, ERK, JNK, and p38 MAPK, and NF-κB components, such as p65 ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). In fact, overexpression of MAPK mRNA in the skin tissue was observed in the AD group ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a significant reduction in inflammation-induced cytokines in skin and lymph nodes was observed after honokiol administration in combination with DNCB treatment [ 10 ]. In the present study, we investigated magnolol, a bioactive lignan found in the bark stripped from the roots, stems, and branches of the Houpu magnolia [ 13 ], a traditional Chinese medicine [ 14 ]. Magnolol has a variety of pharmacological effects, such as anti-anxiety, anti-cancer, anti-depressant, anti-inflammatory, antioxidant, and hepatoprotective properties [ 11 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 The alkaloids in EMW have good biological activity, 9 , 10 which can improve skin pruritus by inhibiting serum Th1/2 cytokines, and suppressing the phosphorylation of JNK, ERK and P38 in the skin. 11 Owing to the multi-component and multi-target characteristics, the mechanisms underlying the therapeutic effects of EMW in AD are unclear. It is difficult to clarify the mechanism of EMW in treating AD using conventional methods.…”
Section: Introductionmentioning
confidence: 99%